Pola Asuh Demokratis Terhadap Penggunaan Smartphone Pada Anak di Lingkungan 18 Binjai - Syahrani A'zmi; Surya , Maulana Andi (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2025)
This research aims to describe the application of democratic parenting patterns towards children’s smartphone usage, the resulting impacts, and the strategies employed by parents in managing smartphone use in the 18 Binjai environment. The method used is descriptive qualitative research with data collection techniques through observation, interviews, and documentation. The informants in this study consist of three parents who have children using smartphones. The research results indicate that all informants apply a democratic parenting pattern, which involves granting limited freedom to children to use smartphones by setting usage duration, selecting age-appropriate content, and accompanying them during usage. The use of smartphones has positive impacts such as enhancing children’s knowledge through educational content such as shalawat songs and animal introduction videos, but it also has negative impacts such as tantrums, lack of focus, and screen dependency. Parents’ strategies to reduce negative impacts include inviting children to play, recite the Quran, perform congregational prayers, and setting an example by limiting smartphone use in front of the children. This study concludes that democratic parenting patterns are effective in managing smartphones, use wisely and in balance, and can reduce negative impacts if practiced consistently and attentively.